2011
DOI: 10.1021/la104597d
|View full text |Cite
|
Sign up to set email alerts
|

Reliable Measurements of Interfacial Slip by Colloid Probe Atomic Force Microscopy. II. Hydrodynamic Force Measurements

Abstract: Here we report a new study on the boundary conditions for the flow of a simple liquid in a confined geometry obtained by measuring hydrodynamic drainage forces with colloid probe atomic force microscopy (AFM). In this work, we provide experimental data obtained using a best practice experimental protocol and fitted with a new theoretical calculation (Zhu, L.; Attard, P.; Neto, C. Langmuir 2010, submitted for publication, preceding paper). We investigated the hydrodynamic forces acting on a silica colloid probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 52 publications
7
75
0
Order By: Relevance
“…Slip and accommodation can vary significantly over surfaces due to local fluctuations in interface properties. In good agreement with the reports of other authors, 29,62 we find that slip parameters generally differ by roughly 10% for measurements on distinct spots on the same substrate. We therefore propose that experiments aiming to investigate the dependence of slip on gas properties are being conducted (1) without lateral displacement of the surfaces relative to each other, (2) as local (with small areas) as possible, and (3) with a good characterization of the interfaces at the very position of the measurements.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Slip and accommodation can vary significantly over surfaces due to local fluctuations in interface properties. In good agreement with the reports of other authors, 29,62 we find that slip parameters generally differ by roughly 10% for measurements on distinct spots on the same substrate. We therefore propose that experiments aiming to investigate the dependence of slip on gas properties are being conducted (1) without lateral displacement of the surfaces relative to each other, (2) as local (with small areas) as possible, and (3) with a good characterization of the interfaces at the very position of the measurements.…”
Section: Discussionsupporting
confidence: 93%
“…29,62 Note that this variation between results obtained on different spots is larger by a factor ∼10 than the error in the determination from the fit. This finding confirms the strong dependence of hydrodynamic forces on the local details of the interface and suggests that in experiments with inherent averaging due to large surface areas (such as flow measurements with micro-channels) correlations between parameters may possibly be weak or not visible.…”
Section: Fig 6 Dependence Of the Fitted Radii For K = 0 Inmentioning
confidence: 91%
“…The oscillating cantilever then scans over the surface of specimen to generate an image with a vertical resolution of around 0.5 nm (Tiede et al, 2008; Zhu et al, 2011). Like SEM and TEM techniques, AFM can be used for investigating the size, shape, structure, sorption, dispersion and aggregation of nanomaterials — the different scanning modes employed in AFM studies include noncontact mode (also called static mode), contact mode and intermittent sample contact mode (also called dynamic mode and tapping mode) (Hinterdorfer et al, 2012; Mavrocordatos et al, 2004; Picas et al, 2012; Sapsford et al, 2011; Song et al, 2011).…”
Section: Modalities For Physicochemical Characterizationmentioning
confidence: 99%
“…Although other expressions for f à have been used in various studies depending on the nature of interacting surfaces, 17,[19][20][21][22][23][24][25] our tests indicated that the physical results remain qualitatively the same as those obtained with Eq. (2).…”
mentioning
confidence: 58%
“…Several works indicated that the slip length depends on the morphology and material of the solid surface. [16][17][18][19][20][21][22][23] Nevertheless, it remains unexplored how the interplay of Casimir forces and hydrodynamic dissipation can affect actuation dynamics of MEMS/NEMS, and we consider this below. The modulation of the magnitude of the Casimir forces can also alter the interplay between dissipation and stiction dynamics, and for this aspect we consider PCMs, where the optical properties alter drastically during amorphous-crystalline phase transitions.…”
mentioning
confidence: 99%